2021
DOI: 10.1016/j.omtn.2021.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Naringin improves sepsis-induced intestinal injury by modulating macrophage polarization via PPARγ/miR-21 axis

Abstract: Naringin exhibited various pharmacological activities. However, its biological function and underlying mechanism in regulating macrophage polarization remain elusive. This study aimed to investigate the regulatory network between naringin and macrophage polarization in sepsis-induced intestinal injury. Cecal ligation and puncture (CLP) was used to establish the animal model of sepsis. Chromatin immunoprecipitation and a luciferase reporter assay were used to determine the interplay between peroxisome prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 45 publications
(53 reference statements)
1
18
0
1
Order By: Relevance
“…In addition, it was reported that the anti-inflammatory effects of NG are regulated by multiple mechanisms including (1) the promotion of macrophage M2 polarization through PI3K/AKT/mTOR signaling pathways; (2) inhibition of multiple inflammation-related signaling pathways (such as NF-κB and MAPK pathways) to reduce the production of inflammation-related factors, thereby suppressing inflammation, and (3) adjustment of the peroxisome proliferator-activated receptor (PPAR)/miR-21 pathway participating in the regulation of inflammation. 46–49…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it was reported that the anti-inflammatory effects of NG are regulated by multiple mechanisms including (1) the promotion of macrophage M2 polarization through PI3K/AKT/mTOR signaling pathways; (2) inhibition of multiple inflammation-related signaling pathways (such as NF-κB and MAPK pathways) to reduce the production of inflammation-related factors, thereby suppressing inflammation, and (3) adjustment of the peroxisome proliferator-activated receptor (PPAR)/miR-21 pathway participating in the regulation of inflammation. 46–49…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it was reported that the anti-inflammatory effects of NG are regulated by multiple mechanisms including (1) the promotion of macrophage M2 polarization through PI3K/AKT/ mTOR signaling pathways; (2) inhibition of multiple inflammation-related signaling pathways (such as NF-kB and MAPK pathways) to reduce the production of inflammation-related factors, thereby suppressing inflammation, and (3) adjustment of the peroxisome proliferator-activated receptor (PPAR)/miR-21 pathway participating in the regulation of inflammation. [46][47][48][49] Bone regeneration involves three successive phases in the induction of new bone regeneration: inflammation, repair, and remodeling phases. As shown in earlier research, prolonged chronic inflammation caused by macrophages of M1 type could induce the absorption of bone tissue, which causes the formation of a fibrous envelope, blocks the combination of bone cells and implants, and ultimately leads to the failure of bone repair.…”
Section: Osteogenic Differentiation Of Mbmscs In the Macrophage-condi...mentioning
confidence: 99%
“…It is considered that transcription factors are fully involved in macrophage activation [32,33]. Recently studies have shown that the key transcription factor Snail1 is essential for macrophage polarization and metastasis in breast cancer though altered GM-CSF secretion [34].…”
Section: Discussionmentioning
confidence: 99%
“…Naringin at dose of 200 mg/kg produced an anti-inflammatory effect by inducing HO-1 expression in macrophages through the AMPK, p38, and Nrf-2 signaling pathways. Naringin also improved sepsis-induced intestinal injury by modulating macrophage polarization via PPARγ/ miR-21 axis (Li et al, 2021).…”
Section: Naringinmentioning
confidence: 96%